Compact Circular Polarized Antenna Design with H-Shaped Slots and Stair Notches for Wireless LAN Application of 2.4 GHz - Abd Rashid, Kamarul Ariffin; Saad, Muhammad Majdi; Abd Aziz, Mohamad Zoinol; Hassan, Nornikman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
This paper presents the design of a circular polarized antenna for wireless communication system. Firstly, the linear polarization antenna is simulated in the CST Microwave Studio. This linear polarization antenna is designed by using double H-shaped slots, coplanar waveguide (CPW) and stair notches at the patch techniques. Then, the truncated corners at the patch are designed to create a circular polarization antenna. The dimension of this circular polarization antenna is 28 mm width x 33 mm length. Both antennas are designed for a single frequency operation band at 2.4 GHz. The return-loss performance of the circular polarized antenna is - 46.785 dB and – 39.758 dB for each simulation and measurement respectively